2016
DOI: 10.1167/iovs.15-18832
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Findings in Eyes With Birdshot Chorioretinitis Using Enhanced-Depth Optical Coherence Tomography

Abstract: Citation: Böni C, Thorne JE, Spaide RF, et al. Choroidal findings in eyes with birdshot chorioretinitis using enhanced-depth optical coherence tomography. Invest Ophthalmol Vis Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Interestingly, in our study, SCF was associated with a higher MD on SAP at baseline, MD being a well-recognized functional parameter reflecting worsening of visual function. We also found a trend toward an association between CT changes and MD at baseline, as also suggested by previous studies [14], but this may simply reflect disease duration. Visual field defects may reflect the inflammatory process within the choroid and/or the retina [7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, in our study, SCF was associated with a higher MD on SAP at baseline, MD being a well-recognized functional parameter reflecting worsening of visual function. We also found a trend toward an association between CT changes and MD at baseline, as also suggested by previous studies [14], but this may simply reflect disease duration. Visual field defects may reflect the inflammatory process within the choroid and/or the retina [7].…”
Section: Discussionsupporting
confidence: 90%
“…In our patients during follow-up, BCVA, MD and FST did not show significant changes, while foveal CT decreased and SCF significantly increased. In previous studies, thin choroids were significantly associated with longer disease duration, suggesting the possibility of disease-related choroidal atrophy [14]. We hypothesize that both choroidal thinning and increase of SCF during follow-up could be a sign of progressive choroidal inflammation and degeneration.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In a study of 86 individuals with BSCR, we showed that enhanced depth imaging optical coherence tomography (EDI-OCT) could identify choroidal lesions that do not correspond to ''birdshot lesions'' and are not apparent on examination of the fundus. 1 In other studies, fundus autofluorescence (FAF) imaging was also able to show abnormalities not identified by clinical examination or other modalities. [2][3][4] FAF identifies lipofuscin accumulation in the RPE and provides information about RPE structure and health.…”
mentioning
confidence: 92%
“…2,3 Previous studies of FAF imaging and BSCR involved small numbers of individuals, and they were primarily descriptive, without extensive comparison to other disease features or visual function. [2][3][4] To expand our understanding of FAF in eyes with BSCR, we performed a prospective study of FAF findings in the same cohort of 86 individuals whose choroids were studied by EDI-OCT. 1 As in that study, we compared imaging findings to demographic and medical factors, clinical examination findings, and multiple measures of visual function. Findings may provide a better understanding of the spectrum of abnormalities associated with BSCR, suggest disease mechanisms, and identify features of the disease that should be monitored in future clinical studies.…”
mentioning
confidence: 99%